MEMAKNAI SPIRIT MISI PELAYARAN CHENG HO SEBAGAI MEDIA INTEGRASI SOSIAL ETNIK TIONGHOA DI INDONESIA YANG BERDEMENSI MULTIKULURALISM - Eko Punto Hendro (Studi Budaya Nusantara, 2018)
The arrival of Laksama Cheng Ho to Indonesia in the past with friendship has actually laid the foundations of a very harmonious relationship between ethnic-ethnic in Indonesia with ethnic Chinese.A multiculturalism approach would be a strategic bid to change other approach models that once existed. By taking the spirit of Cheng Ho’s voyage, this approach is a good new model but not yet tested, the government should wisely adopt a wise civic policy by providing facilities for infrastructure such as moral appeals, encouragement or in the form of conducive legislation. Even if later will happen acculturation process or assimilation let happen by itself and can not be forced.